2021
DOI: 10.1038/s41467-021-22453-0
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter mineralization in modern and ancient ferruginous sediments

Abstract: Deposition of ferruginous sediment was widespread during the Archaean and Proterozoic Eons, playing an important role in global biogeochemical cycling. Knowledge of organic matter mineralization in such sediment, however, remains mostly conceptual, as modern ferruginous analogs are largely unstudied. Here we show that in sediment of ferruginous Lake Towuti, Indonesia, methanogenesis dominates organic matter mineralization despite highly abundant reactive ferric iron phases like goethite that persist throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…Additional experiments by Roden and Urrutia (2002) showed similar results with Geobacter metallireducens and their work also suggests that Fe(II) sorption onto iron-reducing bacteria may further inhibit their ability to carry out iron reduction. Friese et al (2021) observed methanogenesis dominating over iron reduction in sediments in ferruginous Lake Towuti, Indonesia despite the presence of reactive iron(III) phases and attribute this to surface passivation of reactive iron. Our observed increase in Fe(II) content of the ferrihydrite (Figure 3D) over time is also consistent with surface passivation, which may have contributed to our observed results showing that methanogens can outcompete iron-reducing bacteria on longer timescales in the presence of ferrihydrite.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additional experiments by Roden and Urrutia (2002) showed similar results with Geobacter metallireducens and their work also suggests that Fe(II) sorption onto iron-reducing bacteria may further inhibit their ability to carry out iron reduction. Friese et al (2021) observed methanogenesis dominating over iron reduction in sediments in ferruginous Lake Towuti, Indonesia despite the presence of reactive iron(III) phases and attribute this to surface passivation of reactive iron. Our observed increase in Fe(II) content of the ferrihydrite (Figure 3D) over time is also consistent with surface passivation, which may have contributed to our observed results showing that methanogens can outcompete iron-reducing bacteria on longer timescales in the presence of ferrihydrite.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, many studies have shown that iron reduction outcompetes methanogenesis in wetlands and soils when iron is present as a poorly crystalline iron oxide (Sahrawat, 2004;Laanbroek, 2010). However, there are also many instances where methanogenesis and iron reduction occur concomitantly (Slomp et al, 2013;Vigderovich et al, 2019), or where methanogenesis dominates in zones of ferruginous lakes with persistent iron oxides (Lambrecht et al, 2020;Friese et al, 2021). A decreased relative ability of iron-reducers to out-compete methanogens in the presence of well-crystalline iron oxides may explain overlapping zones of iron reduction and methanogenesis in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentary OM is mainly autochthonous (Friese et al, 2021), albeit at low concentrations, with some contribution of fluvially-derived material (Morlock et al, 2019;Hasberg et al, 2019). TOC and siderite concentrations display opposite trends, with highest TOC concentrations found in diatom oozes and green clays (Fig.…”
Section: Core Lithology and Bulk Sedimentmentioning
confidence: 99%
“…One was used to determine the partial pressure of methane using a Thermo Finnigan Trace gas chromatograph (Thermo Fisher Scientific, Waltham, United-States) equipped with flame ionization detector (GC-FID), and the other one was used for carbon isotopic analysis of methane (δ 13 CH 4 ) and carbon dioxide (δ 13 CO 2 ) by isotope-ratio-monitoring gas chromatography/mass spectrometry (irm-GC/MS) on a Trace GC Ultra gas chromatograph (Thermo Fisher Scientific) coupled to a continuous-flow isotope ratio mass spectrometer (Delta V Plus, Thermo Fisher Scientific) as described in Friese et al (2021). Results are reported as δ-values in per mil relative to V-PDB.…”
Section: Pore Water Analysesmentioning
confidence: 99%
See 1 more Smart Citation